Residential real estate production in Curitiba in the 2010s: some reflections - Martins, Fabiana Moro; Pereira, Gislene de Fátima (Pontifícia Universidade Católica de São Paulo, 2021)
Space production as a means of capital reproduction was intensified in Brazil over the last decade, through the financialization of the real estate sector and the execution of the Minha Casa Minha Vida housing program, which encouraged the production of affordable housing by market agents. Considering this scenario, the text presents the results of a research on the multifamily housing developments concluded in the city of Curitiba between 2010 and 2018. The study identifies the agents and characteristics of the projects and their effects on urban space. The expansion of residential real estate production, both numerical and territorial, was confirmed, with a strong presence of publicly traded companies and the employment of different strategic actions according to the then-current economic scenario. This production has reinforced the segmentation and fragmentation of the city space.